Competition between for-profit and industry labels: The case of social labels in the coffee market - Pio Baake; Helene Naegele (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
We model strategic interaction on a market where two labeling organizations compete and firms in duopoly decide which labels to offer. The incumbent label maximizes its own profit, and is challenged by an industry standard which maximizes industry profit. Using a nested logit, the result of this multi-stage game depends crucially on the degree of horizontal differentiation. Joint firm profit always increases with the introduction of the industry standard. The industry standard wants to segment the market and strategically distorts its label quality downwards, such that each firm specializes in a different label. Social welfare however increases with the number of labeled products. A policy imposing a minimum label quality is only binding in the case of strategic quality distortion by the industry standard.
Keywords: L15; D43; L13; 330; product differentiation; certification; nested logit